Art+science: An emerging paradigm for conceptualizing changes in consciousness. Issue 2 (1st December 2012) - Jacques, Claudia
Maurits Cornelis Escher's 1938 lithograph, Cycle, illustrates what mathematical physicist Roger Penrose calls 'impossible objects'. The illusion of three-dimensionality, the innovative use of tessellation, and the incorporation of traditionally figurative elements induce the viewer to perceive the lithographic print as depicting a visually plausible reality built on the deconstructive metamorphosis of man into cube. It is Escher's ability to paradoxically combine the radical oppositions of man and cube, landscape and geometric abstraction into an apparently harmonious composition where shapes repeat with subtle variation and almost imperceptibly transition into radically different shapes that I want to use as a visual paradigm for conceptualizing the shifts in human consciousness in the digital age. Roger Penrose, path-breaking theorist of consciousness as a physical but non-computational process, was inspired by and inspired Escher. Penrose's provisional concepts of consciousness, time and space can be visually compared to Escher's earlier man-cube renderings, where each of these individual design elements allows the transition to another shape. In other words, Penrose's theories, like Escher's design concepts, illustrate a moment of transition in consciousness theory. As in Escher's Cycle, the individual elements are being continually redefined, reshaped and revealed. Each may be a unique distortion of the previous, but this does not mean that it is disconnected or independent of the final outcome. These distortions are transitional elements that lead us visually to the other side of the composition. Radical transformations and developing connectedness in the boundaries between art, technology and science function like the individual elements in Escher's Cycle. As we try to define the shifts in human consciousness occurring in the digital age, visually speaking, we are focusing on only one element right in the middle of an Escher metamorphosis, unable to see exactly how this element will be part of the completed design. This thought can be both frightening and liberating: frightening because we humans are used to relying on boundaries and predictable outcomes to feel a sense of control, liberating because anything and everything is possible and the changes will occur naturally as part of the transition. If Escher teaches us anything, it is that each piece in the meta-morphosis is needed to complete the big picture.